Pengaruh Konvergensi IFRS terhadap Manajemen Laba dengan Mekanisme Corporate Governance sebagai Variabel Moderating pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014 - Hasna Katsurayya; Lediana Sufina (Jurnal Keuangan dan Perbankan, 2016)
The tendency to generate high profits lead management to select accounting policies and apply methods that can provide a better return. It is often known as the earnings management. The purpose of this study is to find out the effect of convergence of IFRS pon earnings management with corporate governance as moderating variable in property and real estate company listed on the Indonesia Stock Exchange in 2010-2014. Convergence of IFRS as an independent variable is proxied by dummy variable. Accrual-earnings management is measured by the value of discretionary accruals and real-earnings management is measured by the value of abnormal cash flows from operations. Mechanism of corporate governance as a moderating variable considering the characteristics of the commissioners, audit committee, auditor quality, institutional ownership and the managerial ownership. The results show that the convergence of IFRS influence real-earnings management significantly,but doesn’t has significant effect on accrual-earnings management. Convergence of IFRS effect real-earnings management significantly, while it is moderated by institutional ownership. Institutional ownership has moderating effect to the convergence of IFRS and real-earnings management